Training On News Writing for Online Media - sapanti, intan rawit (Muhammadiyah University Press, 2018)
AbstractThe aim of this community service are to provide the participant as the commitee member of Aisyiyah the knowledge of basic journalism in order they could write a good news to be published on their official media. Based on the observation and request from the Aisyiyah Organization, they have a problem when writing the article/news because the lack understanding on basics journalism and news writing technique. The method used in this training were lecturing session, discussion and direct assistance on writing the news. There were 30 representatives of the Aisyiyah Commitee from branch and regional office invited to this activity. The result of the training shows a significant improvement fromt he participant that can be seen on the pre-test and post-test result. There is a quite significant increase of 12% which is shows that the training material and method can be easily be understood well by the participant. At the end of the training, the participant are able to write a proper news and article to be published on their official website.Keywords: news writing, online media, writing technique, journalism, community services